Compreendendo o comportamento de redução do desperdício alimentar doméstico: aplicação do Modelo Transteórico e da Teoria da Busca Racional de Metas - Floriano, Mikaela Daiane Prestes (Universidade do Vale do Rio dos Sinos, 2024)
To achieve the Sustainable Development Goals, one of the main challenges is reducing food loss and waste. Households are among the main contributors to this problem, making the reduction of waste at the consumer level essential for improving sustainable development indices. However, the complexity of human behaviors makes it difficult to recognize the elements and psychological responses that can facilitate the adoption of anti-waste actions. This situation is further aggravated by admitting that people present important differences in their behavioral and personal characteristics, resulting in the inability to implement strategies aimed at behavioral changes for any consumer profile. Therefore, this thesis developed a theoretical model integrating the Theory of Rational Goal Pursuit and the Transtheoretical Model to achieve the objective of analyzing the influencers of household food waste reduction behavior considering the consumers' stage of readiness to change. The objective of this thesis was achieved by conducting a survey with 429 consumers responsible for managing their family's food. To test the proposed model, PLS-SEM and multigroup analysis were used. The developed model was composed of nine constructs: procurement goals, approval goals, attitude, subjective norms, perceived behavioral control, motivation, intention, waste reduction behavior and stages of readiness for change. Based on the stages of readiness, it was identified that consumers present several similarities and distinctions regarding demographic, consumption and behavioral aspects. The results of the study indicated that procurement and approval goals have, respectively, direct effects on attitude and subjective norms in the four segments analyzed. However, only in the Recognition and Preparation stages did procurement goals influence consumer motivation. Approval goals did not have direct effects on motivation, having indirect effects on behavior in the Recognition and Maintenance stages. Motivation directly influenced behavioral intention and, like procurement goals, had an indirect effect on food waste reduction behavior. Perceived behavioral control acted as a moderating variable in the motivation-intention relationship. The negative moderating effect indicated that when there are active individual goals, deprivation of control can stimulate consumers' intention to reduce waste. This thesis proves the importance of personal goals, social goals and motivation in explaining waste reduction behavior. It also attests to how the determinants of anti-waste actions act in different ways due to the degree of consumer involvement with sustainable food practices. The findings of this study can guide interventions aimed at combating the reduction of household food waste for four different consumer profiles.
Keywords: Objetivos pessoais; Objetivos sociais; Motivação; Segmentação; Consumo alimentar sustentável; Mudança de comportamento; Personal goals; Social goals; Motivation; Segmentation; Sustainable food consumption; Behavior change; ACCNPQ::Ciências Sociais Aplicadas::Administração